IMPLEMENTASI ENVIRONMENTAL ACCOUNTING MENUJU USAHA MIKRO RAMAH LINGKUNGAN PADA USAHA MIKRO GERABAH KAMPUNG KOSAMBI KECAMATAN CIRUAS KABUPATEN SERANG - Marina Amelia (TRIDAYA: Jurnal Pengabdian kepada Masyarakat, 2025)
Production activities in micro businesses such as pottery making in Kosambi Village often have a negative impact on the environment, such as poorly managed waste disposal and excessive exploitataion of natural resources. The overcome this, the Community Service Team (PKM) from Pamulang University Serang Accounting Study Programme provided counselling on the application of the concept of environmental accounting to pottery craftsmen. Environmental accounting is a system for identifyng, measuring, and communicating information related to the environmental costs and benefits of economic activity.By applying it, artisans can quantitatively measure the environmental impact of operations such as raw material use and waste disposal. This enables desicion-making to reduce environmental footprint, improve production cost efficiency through resource saving and optimised waste management, and comply with environmental regulations. Strategies delivered include energy efficiency, waste recycling, and selection of environmentally friendly raw materials. Succesful implementation of environmental accounting requires goverment support in funding, training, market access, industrial waste management, and partnerships with research institutions. With good implementation, pottery businesses can be sustainable by minimising environmental impacts. Keywords: Environmental Accounting, Green Accounting, Micro business